2015
DOI: 10.1038/srep08024
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of agricultural intensification on ability of natural enemies to control aphids

Abstract: Agricultural intensification through increasing fertilization input and cropland expansion has caused rapid loss of semi-natural habitats and the subsequent loss of natural enemies of agricultural pests. It is however extremely difficult to disentangle the effects of agricultural intensification on arthropod communities at multiple spatial scales. Based on a two-year study of seventeen 1500 m-radius sites, we analyzed the relative importance of nitrogen input and cropland expansion on cereal aphids and their n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 54 publications
2
72
1
3
Order By: Relevance
“…Reduced biological control cost soybean farmers about $58 million per year due to reduced yield and increased pesticide use [4]. Similarly, Chinese researchers found in a two-year study of seventeen 1500 m-radius sites in China, that input of nitrogen fertilizer and cropland expansion compromised the ability of natural enemies to control cereal aphids leading to a disturbance of interspecific relationships thus enhancing reliance on pesticides [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced biological control cost soybean farmers about $58 million per year due to reduced yield and increased pesticide use [4]. Similarly, Chinese researchers found in a two-year study of seventeen 1500 m-radius sites in China, that input of nitrogen fertilizer and cropland expansion compromised the ability of natural enemies to control cereal aphids leading to a disturbance of interspecific relationships thus enhancing reliance on pesticides [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhao et al (2015) found in a two-year study of 17, 1500 m-radius sites in China, that input of nitrogen fertiliser and cropland expansion compromised the ability of natural enemies to control cereal aphids leading to a disturbance of the interspecific relationships and enhancing reliance on pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…In previous study, we found that agricultural intensification can destabilize the interspecific relationship and lead to biodiversity loss. Additionally, increasing nitrogen fertilizer input could benefit cereal aphids more than their natural enemies, leading to biocontrol loss in agroecosystem [7]. Now, we found that another factor, cropland expansion (landscape change) could lead to pest outbreak at large spatiotemporal scale.…”
mentioning
confidence: 87%